(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Human Development Index is a composite index to measure the development of human resources in each country and there lies four indicators of life expectancy, income per capita, the average number of years studying and hope to the number of years of education will be formed. This article reviews educational system in the State of Uttarakhand, theoretically. Countries, according to the Human Development Index rates countrieswith high human development, and human development countries with medium and low human development countries are divided. Data is mostly taken from official government websites, books and other research works till date. We used the content analysis method in this case study. The objective of the presented research paper is to Study relationship between educational infrastructure and improvement in HDI, as it is calculated by the geometric mean (equally-weighted) of life expectancy, education, and GNI per capita. The effect of education on human development in the Studied countries is much higher than life expectancy and per capita income. The findings of the study reveals special educational requirements in the hilly districts of the Uttarakhand.